Underlying mechanism of electrospun starch-based nanofiber mats to adsorb the key off-odor compounds of oyster peptides - Linfan Shi; Zhouru Li; Shiqin Qing; Zhongyang Ren; Ping Li; Songnan Li; Wuyin Weng (Food Chemistry: X)
The solid-phase adsorption principles and fundamental mechanism of isobutyric acid, 1-octen-3-ol, and octanal (three key off-odor compounds of oyster peptides) were explored using electrospun octenyl succinylated starch-pullulan (OSS-PUL) nanofiber mat. The nanofiber mats had selective adsorption behaviors as indicated by the selective adsorption rates of isobutyric acid, 1-octen-3-ol, and octanal, which were 94.96%, 85.03%, and 65.36%. The contents of the II-type inclusion complexes (ICs) formed with the nanofiber mats by the three off-odor compounds mentioned above were significantly different. The mean fiber diameter of the octanal/nanofiber mat IC with the highest content of II-type IC was significantly decreased (p < 0.05). In contrast, the isobutyric acid/nanofiber mat IC did not significantly change. The findings suggested that nanofiber mats interacted most strongly with octanal and weakly with isobutyric acid. This study will provide the theoretical foundation for deodorizing aquatic products using electrospun starch-based nanofiber mats.